Improving Critical Thinking Skills Using Nature-Based Learning Media In Children At Tk Rukun Lingkar Barat Kota Bengkulu - Yuliza, Milsi; Haryono, Mimpira; Bendriyanti, Rita Prima (Early Childhood Research and Practice, 2025)
This study is a classroom action research that aims to determine the improvement of children's critical thinking skills through the use of nature-based learning media in Rukun Kindergarten, Lingkar Barat, Bengkulu City. The subjects of the study consisted of 15 children in group B. The study was conducted in two cycles, which included the planning, implementation, observation, and reflection stages. Data were collected through direct observation and documentation of learning activities, then analyzed descriptively qualitatively-quantitatively. The quantitative aspect is in the form of the percentage of children's critical thinking skills, while the qualitative aspect includes descriptions of children's behavior, interactions, and responses during learning. The results of the study showed that children's critical thinking skills in the first cycle reached 70%, which was categorized as Developing According to Expectations. After improvements and variations in nature-based learning media were made, in the second cycle there was a significant increase to 95%, categorized as Developing Very Well. This shows the effectiveness of nature-based learning media in facilitating the development of children's critical thinking. The study was stopped in the second cycle because the objectives had been optimally achieved.